2022
DOI: 10.2147/ijgm.s343259
|View full text |Cite
|
Sign up to set email alerts
|

Mutations in the TTN Gene are a Prognostic Factor for Patients with Lung Squamous Cell Carcinomas

Abstract: To analyze the relationship between titin (TTN) mutation gene and tumor mutational burden (TMB) and the with prognosis of lung squamous cell carcinomas (LUSC), and to explore the feasibility of TTN as a potential prognostic marker of for LUSC. Methods: We analyzed the somatic mutation landscape of LUSC samples using datasets obtained from The Cancer Genome Atlas (TCGA) and International Cancer Genome Consortium (ICGC) databases. Sequence data were divided into wild and mutant groups, and differences in TMB val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…In CC patients, the most common oncogenic mutation is P53 mutation, accounting for more than 60% 30 32 . A study delineated that the TTN mutant may be a potential predictor in using immune checkpoint inhibitors in lung cancer patients 33 , 34 . However, the TTN mutant has not been reported in CC.…”
Section: Discussionmentioning
confidence: 99%
“…In CC patients, the most common oncogenic mutation is P53 mutation, accounting for more than 60% 30 32 . A study delineated that the TTN mutant may be a potential predictor in using immune checkpoint inhibitors in lung cancer patients 33 , 34 . However, the TTN mutant has not been reported in CC.…”
Section: Discussionmentioning
confidence: 99%
“…CX3CR1 [441], S100A12 [442], PF4 [443], MPO (myeloperoxidase) [444], WNT7A [445], SLC6A4 [446], BDNF (brain derived neurotrophic factor) [447], CXCL10 [448], NEK7 [449], CYP1B1 [450], ABCA3 [451], TRIB3 [452], PCSK9 [453], FGF2 [454], ACKR4 [455], FASN (fatty acid synthase) [456], VIP (vasoactive intestinal peptide) [457], KL (klotho) [458], BMPR2 [459], APOA1 [323], TLR3 [460], CCR2 [461], TLR7 [462], CAV1 [463], WWC2 [464], TFPI (tissue factor pathway inhibitor) [465], EPAS1 [466] and CCDC40 [467] could serve as a potential therapeutic for pulmonary hypertension treatment. A previous study reported that the genes include CX3CR1 [468], CSF2 [469], CLDN18 [470], TRIM58 [471], PF4 [472], FFAR2 [473], MPO (myeloperoxidase) [474], CD5L [475], SH3GL2 [476], ITGA2B [477], S100A8 [478], VEGFD (vascular endothelial growth factor D) [479], CXCL11 [480], IL1A [481], WNT7A [482], SSTR1 [483], AQP4 [484], SCD (stearoyl-CoA desaturase) [485], SLC6A4 [486], BDNF (brain derived neurotrophic factor) [487], CXCL10 [488], ODAM (odontogenic, ameloblast associated) [489], CASP5 [490], CCL8 [491], TMEM100 [492], S100A9 [493], IL1B [494], CXCR1 [495], CXCR2 [496], WNT3A [497], BMI1 [498], CYP1B1 [499], FCN3 [500], TTN (titin) [501], SHISA3 [502], AZGP1 [503], ABCA3 [504], CD36 [505], EDNRB (endothelin receptor type B) [506], BTNL9 507], CEBPA (CCAAT enhancer binding protein alpha) [508], TRIB3 [509], TNNC1 [510], PCSK9 […”
Section: Discussionmentioning
confidence: 99%
“…TTN mutations associated with human conditions include nonsense mutations, frameshift mutations, missense mutations, and splice site mutations. Studies have reported that TTN missense mutations are correlated with lung squamous cell carcinoma [ 42 , 43 ]. Our study also proved that missense mutations account for the dominant mutations in patients with THCA.…”
Section: Discussionmentioning
confidence: 99%